PENGARUH KUALITAS PRIBADI KONSELOR TERHADAP EFEKTIVITAS LAYANAN KONSELING DI SEKOLAH - Mudjijanti, Fransisca (Widya Warta, 2014)
The problems of this research were 1) whether or not the quality of counselor’s personality influences the effectiveness of counseling services in schools and 2) which characteristic(among the seven) of counselor’s personality is most influential toward the effectiveness of counseling services in schools. The analysis revealed the value of 0.855, which suggests thatthe correlation between the quality of counselor’s personality and the effectiveness of counseling services in schools was of very high degree. The analysis also indicated the coefficient of determination R2 values obtained was 0.731 45.4%, which means that the effectiveness of counseling services in schools was affected by the variable quality of private counselors. While, the t-test results showed that there was some difference of influence of the characteristics of counselor’s personality toward the effectiveness of counseling services in schools. The characteristic of counselor’s personality which is most influential toward the effectiveness of counseling services was the awareness of cultural experience, because it had the highest calculation value t, namely 4.792.